Leading sector determinants as regional competitiveness in the maluku province of indonesia - SYAWAL ZAKARIA (International Journal of Multidisciplinary Research and Studies, 2023)
The Moluccas (Maluku) Province of Indonesia consists of an archipelago with rich natural resources on land and at sea. The potential for this large natural resource should have made this particular province more prosperous than other provinces in Eastern Indonesia, but the opposite has happened. This study aims to determine the leading sectors of regional competitiveness in Maluku Province, Indonesia. The analytical method used is Klassen Typology, Location Quotient (L.Q.), and Shift Share. The study results found three of the sixteen leading sectors had very high regional competitiveness: sector C of the Manufacturing Industry, G.I. Trade and Provision of Food and Beverage Accommodation, and H.J. Transportation. Meanwhile, the sector with the lowest regional competitiveness is Water Procurement, Waste Management, and Recycling. By determining the leading sector as regional competitiveness, it is hoped that it can become the basis for policy formulation by the Maluku Provincial Government to improve the welfare of the local community.